PENERAPAN REALISTIC MATHEMATICS EDUCATION ( RME ) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTS.AL-MA’ARIF NU SINAH TAHUN PELAJARAN 2016/2017 - Darmawati, Siti; Sutarto, Sutarto; Yuntawati, Yuntawati (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Students learning outcomes especially on the subject matter of Circle are low. This is caused by teachers less to relate mathematics to the real world. Therefore, in order to increase student interest and learning outcomes, it needs a learning model that relates to daily life. The purpose of this research is to know the increase of students interest and learning outcomes by applying Realistic Mathematics Education at VII grade students of MTs. AL-Ma'arif NU Sinah in academic year 2016/2017. The type of this research is classroom action research conducted in two cycles. The data of student learning outcomes collected through evaluation test and the data of student interest is collected through questionnaire. Based on the results data analisys can be seen the increase in the percentage of student learning outcomes from 47.82% to 87.5%. it is known that the implementation of Realistic Mathematics Education (RME) able to increase the student interest and learning outcomes at VIII grades students of MTs.AL-Ma'arif NU Sinah on the subject matter of Cycle of lesson year 2016/2017